Effects of anodisation parameters on thin film properties: a review. Issue 6 (13th April 2017) - Wong, Y. H.; Affendy, M. G.; Lau, S. K.; Teh, P. C.; Lee, H. J.; Tan, C. Y.; Ramesh, S.
Abstract : Electrochemical anodisation is a well-received method in the complementary metal-oxide-semiconductor field as it is advantageous; best performed at room temperature which translates into being more affordable and a simple alternative to form nano-structured oxide films for different metals. The quintessential parameters involved allow numerous formations of metal oxide films according to desired morphology and thickness. Therefore, this paper aims to review the effects of anodising parameters such as applied voltage, concentration, temperature, time, current density and post-anodisation annealing among them.